S16 A Large, Prospective, Multicentre Study Evaluating the Survival of Patients with Malignant Pleural Effusion According to the Underlying Cell Type. (19th November 2012) - Clive, AO; Hooper, CE; Fysh, ETH; Tobin, C; Morley, AJ; Zahan, N; Sellar, C; Bhatnagar, R; Medford, AR; Lee, YCG; Maskell, NA
Abstract : Malignant pleural effusion (MPE) is a common clinical problem, which causes significant morbidity and has a variable prognosis. This is the largest series to date evaluating the survival of patients with MPE according to their underlying cell type. Methods: We prospectively collected data on patients presenting with MPE from two large pleural services over a 3 year period. All patients gave written informed consent. Patients were followed up for a minimum of 9 months or until death or loss to follow up (whichever was sooner). For survival analysis, the log rank (Mantel-Cox) test was applied to Kaplan Meier survival curves. Results: Data was collected on 466 patients. The median age of the patients was 71 (IQR 65–79) and 63% were male. 56% of effusions were right sided and 41% patients had an effusion occupying >50% of the hemithorax. 73% of patients had confirmation of pleural malignancy based on cytology or pleural biopsy, 21% had a presumed malignant effusion with confirmed malignancy elsewhere and 6% had a radiological diagnosis. Patients: with a pleural effusion secondary to mesothelioma (n=148) had the longest median survival (MS) at 339 days. This is significantly longer than those effusions caused by lung cancer (n= 127, MS 71 days) (95% CI –0.56–4.45, p <0.0001). Cell types with an intermediate survival, included gynaecological malignancy (n=33; MS=268 days), urological cancer (n=11; MS=220 days), gastrointestinal malignancy (n=16; MS 268 days), haematological malignancy (n=27; median survival 204 days) and breast cancer (n=48; MS 204 days). Lung cancer, adenocarcinoma of unknown primary (n=9; MS 87 days) and sarcoma (n=6, MS 65.5 days) had the shortest survival. The Kaplan-Meier survival curve for the 3 largest groups is shown in the figure. Conclusions: Selecting the most appropriate strategy for management of malignant pleural effusion depends on patient choice, their clinical condition and the perceived prognosis. This data confirms that the survival of patients with malignant pleural effusion varies widely depending on the site of their primary malignancy. Accounting for this may help to better inform patients of their prognosis and aid clinical decision making.